2008
DOI: 10.1111/j.1439-0310.2008.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Mating Success at Various Nutritional States in the Yellow Dung Fly

Abstract: Mating success not only depends on genetic quality, but also equally on environmental factors, most prominently food availability. We investigated the interactive effects of nutritional state and body size on mating success and copula duration in yellow dung fly males (Scathophaga stercoraria; Diptera: Scathophagidae) of three body size selection lines in the laboratory in both non-competitive (single) and competitive (group) situations. Adults require protein and lipids from prey to reproduce, as well as suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Depleted energy reserves have previously been shown to decrease male mating propensity, capture success and copulation duration in S. stercoraria [55,56], although in contrast to this study, Ward & Simmons [55] found a more pronounced decrease in mating propensity when energy depleted males were paired with females in the absence of dung. Alternatively, the attempt rate of large males in non-competitive environments may be inherently lower than that of small males, as suggested by Blanckenhorn et al [57], who found lower mating success for larger males in the laboratory under noncompetitive conditions, although it is unclear whether females influenced mating success in this experiment.…”
Section: Discussionmentioning
confidence: 67%
“…Depleted energy reserves have previously been shown to decrease male mating propensity, capture success and copulation duration in S. stercoraria [55,56], although in contrast to this study, Ward & Simmons [55] found a more pronounced decrease in mating propensity when energy depleted males were paired with females in the absence of dung. Alternatively, the attempt rate of large males in non-competitive environments may be inherently lower than that of small males, as suggested by Blanckenhorn et al [57], who found lower mating success for larger males in the laboratory under noncompetitive conditions, although it is unclear whether females influenced mating success in this experiment.…”
Section: Discussionmentioning
confidence: 67%
“…Possible explanations include (i) only smaller males seek copulations on pomace (e.g. larger males on pomace are only there to feed), (ii) smaller males are better at searching for females on pomace (Blanckenhorn et al 2008), and/or (iii) females are able to exert mate choice on pomace and have a preference for smaller males. Any combination of these three mechanisms supports the interpretation of an alternative mating tactic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that generating empirical measurements of male parameters might be more important than measuring these for the females. Although our model was specifically developed to simulate a specific taxon, the results are likely to be more widely applicable as pre-mating struggles in insects are common (Thornhill, 1980;Dennis et al, 1986;Otronen, 1989;Arnqvist, 1992;Crean & Gilburn, 1998;Blanckenhorn et al, 2000;Eberhard, 2002;Takami, 2002;Miller, 2003;Teder, 2005;Puniamoorthy et al, 2008), and body size often aids both persistence and resistance (Arnqvist et al, 1996;Crean & Gilburn, 1998;Blanckenhorn et al, 2000Blanckenhorn et al, , 2008Teder, 2005). Studies of the effects of male size on mount rate do not seem to have been carried out in the other systems so it is unclear whether a negative correlation between mount rate and size is a common feature of insects that display pre-mating struggles.…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic that often affects both persistence and resistance during pre‐copulatory struggles in insects is body size (Arnqvist et al. , 1996; Crean & Gilburn, 1998; Blanckenhorn et al. , 2000, 2008; Teder, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation